Review on robot-assisted polishing: Status and future trends. (April 2023) - Ke, Xiaolong; Yu, Yongheng; Li, Kangsen; Wang, Tianyi; Zhong, Bo; Wang, Zhenzhong; Kong, Lingbao; Guo, Jiang; Huang, Lei; Idir, Mourad; Liu, Chao; Wang, Chunjin
Highlights: This review introduced the comprehensive background of robot-assisted polishing. Typical robot-assisted polishing methods were presented and discussed. Current development of polishing force control in robot-assisted polishing was discussed. Error analysis and compensation technology of robot-assisted polishing was discussed. Future research directions of robot-assisted polishing were summarized. Abstract: Nowadays, precision components have been extensively used in various industries such as biomedicine, photonics, and optics. To achieve nanometric surface roughness, high-precision polishing is mandatory. Compared with the conventional polishing techniques, the robot-assisted polishing has the advantages of flexible working ranges and low cost. Therefore, it has been more widely deployed in demanding polishing tasks. However, few review articles were found on this topic to provide a general progress on the development of the robot-assisted polishing technology. This paper reviews the recent advancement of the robot-assisted polishing. Firstly, the integration of robots with various polishing techniques is overviewed, followed by the introduction of the research status of constant force control in robot-assisted polishing. Then, the errors in typical robot-assisted polishing systems are analyzed, together with the corresponding compensation methods. At last, the future trends in the development of robot-assisted polishing are discussed. This review is intended as a roadmap for researchers or engineers who are interested in robot-assisted polishing or machining.